PENERAPAN PENDEKATAN COOPERATIVE LEARNING STAD UNTUK MENINGKATKAN HASIL BELAJAR PKn PADA SISWA SEKOLAH DASAR - Sri Wahanani (Tarbawi : Jurnal Pendidikan Islam, 2016)
The purpose is achieved in this research is to describe the approach of cooperative learning STAD model on the learning process Civics, to describe the impact of the learning model cooperative learning model of STAD in teaching civics of the higher institutions of the state in the government structure the central level for students of fourth grade Negeri 2 KandangrejoKlambu District Grobogan Regency in the 1st semester of 2015/2016. The research was conducted in grade IV of State Elementary School 2 KandangrejoKlambu Sub-District Grobogan District. The number of students in grade IV is 25 students, consisting of 13 men and 12 women. Implementation of improvement in two cycles, each cycle through planning, implementation, observation, and reflection. The implementation schedule of each cycle is for Cycle I on Monday, September 14, 2015 and October 19, 2015 with a time allocation of 4 x 35 minutes (2 x meetings). Cycle II on Monday, October 26, 2015 and 2 November 2015 with a time allocation of 4 x 35 minutes (2 x meetings). In cycle I there are 18 students who got the value of complete or 72%. In cycle II, there are 23 students from 25 students got the value of complete or 92%. Not all students complete and there are still two students who have not completed, this is because students' cognitive abilities are slow. The conclusion of this research is the application of STAD Cooperative Learning learning model is very effective to increase students' courage in opinion, enable students in discussion, and understanding and mastery of students to the material. the use of real learning media can emrangsang thoughts, feelings, concerns, and the willingness of students so that they can motivate student learning. Keywords: Cooperative Learning, Model STAD, Learning outcomes Tujuan penelitian ini adalah untuk mendiskripsikan penerapan pendekatan Cooperative Learning model STAD pada proses pembelajaran PKn dan pengaruhnya terhadap pembelajaran PKn tentang lembaga-lembaga tinggi negara dalam susunan pemerintahan tingkat pusat bagi siswa kelas IV SD Negeri 2 Kandangrejo Kecamatan Klambu Kabupaten Grobogan pada semester 1 tahun 2015/2016.Penelitian ini merupakan penelitian tindakan kelas yang dilaksanakan di kelas IV Sekolah Dasar Negeri 2 Kandangrejo Kecamatan Klambu Kabupaten Grobogan. Jumlah siswa kelas IV sebanyak 25 siswa, terdiri dari 13 laki-laki dan 12 perempuan.Pelaksanaan perbaikan dilakukan dalam dua siklus, setiap siklus melalui tahap perencanaan, pelaksanaan, pengamatan, dan refleksi. Adapun jadwal pelaksanaan masing-masing siklus adalah untuk Siklus I pada hari Senin, tanggal 14 September 2015 dan 19 Oktober 2015 dengan alokasi waktu 4 x 35 menit (2 x pertemuan). Siklus II pada hari Senin, tanggal 26 Oktober 2015 dan 2 November 2015 dengan alokasi waktu 4 x 35 menit (2 x pertemuan).Pada siklus I ini terdapat 18 siswa yang mendapat nilai tuntas atau 72 %. Pada siklus II ini terdapat 23 siswa dari 25 siswa mendapat nilai tuntas atau 92%. Simpulan dari penelitian ini adalah penerapan model pembelajaran Cooperative Learning STAD sangat efektif untuk meningkatkan keberanian siswa dalam berpendapat, mengaktifkan siswa dalam diskusi, serta pemahaman dan penguasaan siswa terhadap materi. Kata kunci: Cooperative Learning, Model STAD, Hasil Belajar